2021
DOI: 10.3390/molecules26226909
|View full text |Cite
|
Sign up to set email alerts
|

Stinging Nettle (Urtica dioica L.) as a Functional Component in Durum Wheat Pasta Production: Impact on Chemical Composition, In Vitro Glycemic Index, and Quality Properties

Abstract: Stinging nettle (Urtica dioica L.) is a good source of biologically active compounds with proven beneficial health effects. This study aimed to investigate the effect of nettle herb supplementation on chemical composition, including the content of selected minerals and pigments, the in vitro glycemic response, and the cooking and sensory quality of extruded pasta. Tagliatelle-shaped pasta was produced under semi-technical scale by partial replacement of durum wheat semolina with 0, 1, 2, 3, 4, and 5% of lyophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 33 publications
3
26
1
Order By: Relevance
“…OCT is influenced by various factors such as the raw materials used for pasta preparation [37], the parameters of the technological process [37], and the type of pasta [38]. Some authors found a positive correlation between the total dietary fiber content in pasta and OCT [39,40]. By contrast, a negative relationship was found in the present study and in others [33,41].…”
Section: Cooking Quality Of Pastacontrasting
confidence: 57%
See 2 more Smart Citations
“…OCT is influenced by various factors such as the raw materials used for pasta preparation [37], the parameters of the technological process [37], and the type of pasta [38]. Some authors found a positive correlation between the total dietary fiber content in pasta and OCT [39,40]. By contrast, a negative relationship was found in the present study and in others [33,41].…”
Section: Cooking Quality Of Pastacontrasting
confidence: 57%
“…This suggests that different sources of fiber and ratios of soluble to insoluble fiber can have varied effects on the cooking properties of pasta. At a high amount, fiber often negatively influences the cooking properties of pasta due to the disruption of the starch-protein matrix dough during dough mixing and can swell rapidly during pasta cooking [40]. On the other hand, some nontraditional ingredients with high fiber content can have no negative effect on the quality of pasta or even increase its cooking quality [2,42].…”
Section: Cooking Quality Of Pastamentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing the cooking loss, due to the enrichment of pasta with KBL, may also be a result of the weakening of the gluten matrix, which resulted in weaker binding of starch granules in the structure of the pasta amylose leaching and solubilization of some salt-soluble proteins into the water during cooking [ 55 ]. Other authors also observed an increase in cooking loss in pasta enriched with new ingredients [ 18 , 50 , 56 ].…”
Section: Resultsmentioning
confidence: 81%
“…The basic raw material used in the production of pasta is wheat semolina, which is hydrated to the appropriate level and then pressed or formed by the use of rolls. Due to its widespread consumption and universal use in nutrition, pasta is often used as a matrix for introducing new, biologically active compounds and nutrients [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%